(untitled) (SMC Journal Shadananda Multiple Campus, 2026)
The aim of the review is to assess the major educational policies and reform initiatives of the country, and the provisions from the perspective of the shift from the modernist to the postmodernist approach, and their implications for the country’s current educational system. For the review, researchers purposively selected 52 sources from the pool of national policy documents, the country’s constitutional legal provisions, government education policies and plans, and journal articles published between 1956 and 2025, based on thematic relevance. The research concludes that the shift from the modernist to the postmodernist approach of the education system of the country has taken place in three phases of the introduction of Western-style formal education by the Rana regime, the expansion and privatization of education from the year 1950, and the establishment of a monolingual, nationalist, and centralized education system as embodied by the National Education System Plan of the country in the year 1971. The shift from the modernist to the postmodernist approach to the education system of the country has become possible from the year 1990, and the major developments of the period include the promotion of linguistic diversity and the decentralized system of governance of the country’s education system, the provision of inclusive education, the decentralization of the curriculum of the country’s education system with the help of information and communication technology. The review concludes that the country’s education system has shifted from a modernist to a postmodernist approach and continues to evolve within that framework.